Validity of NRS-2002, MUST, MST, and MNA-SF as first-step screening tools for malnutrition based on GLIM criteria in older adults - Xuan Le Thi Thanh; Phuong Duong Thi; Huong Le Thi; Toi Phung Lam; Dung Nguyen Quang; Lan Nguyen Thi Huong; Thuc Luu Thi My; Hong Nguyen Thi Thuy (Clinical Nutrition Open Science, 2025)
Summary: Background: According to the Global Leadership Initiative on Malnutrition (GLIM), screening for malnutrition risk using a validated tool is the first essential step in the diagnostic process. This study aimed to compare the diagnostic performance of four commonly used tools - Mini Nutritional Assessment Short Form (MNA-SF), Nutritional Risk Screening 2002 (NRS-2002), Malnutrition Screening Tool (MST), and Malnutrition Universal Screening Tool (MUST) as a first-step screening instrument for hospitalized older adults according to the GLIM criteria. Methods: A prospective cross-sectional study was conducted among 200 hospitalized elderly patients at Hanoi Medical University Hospital, Vietnam, between September and December 2023. Nutritional risk was screened at admission using MNA-SF, NRS-2002, MST, and MUST. Malnutrition was diagnosed using GLIM criteria and full MNA. Results: Of the 200 patients, malnutrition risk or malnutrition was identified in 65.0% by MNA-SF, 45.0% by MST, 45.5% by MUST, and 45.0% by NRS-2002. According to full MNA, 58.5% of patients were at risk of malnutrition, and the prevalence of malnutrition based on GLIM criteria (without prior screening) was 54.0%. Using different screening tools as the first step for GLIM, MNA-SF showed the best performance (sensitivity: 100%, specificity: 82.9%, AUC: 0.91), followed by MUST (AUC: 0.88), NRS-2002 (AUC: 0.87), and MST (AUC: 0.83). Agreement with GLIM-defined malnutrition was high for all tools (Cohen's kappa: 0.81–0.95), with the highest for NRS-2002 (kappa = 0.93). Conclusions: All four screening tools showed good diagnostic performance for detecting malnutrition based on GLIM criteria. Among them, MNA-SF showed the highest accuracy, making it the most effective first-step tool for screening and detecting malnutrition in elderly hospitalized patients based on the GLIM criteria.